COVID-19 symptom severity and duration among outpatients, July 2021-May 2023: The PROTECT observational study - Bhavya Vashi; Kristen Pettrone; Claire S. Wilson; Josh G. Chenoweth; Joost Brandsma; Melissa K. Gregory; Pavol Genzor; Deborah A. Striegel; Richard E. Rothman; Bhakti Hansoti; Gideon D. Avornu; Breana McBryde; et al. (PLoS ONE, 2025)
Introduction With the emergence of new SARS-CoV-2 variants has come significant variations in disease manifestation, severity, and duration in non-hospitalized infected patients. To characterize symptom patterns and risk factors associated with symptom severity and duration, COVID-19 and influenza-like illness (ILI) outpatients and their contacts were enrolled at two sites in the United States of America and one site in Thailand. Methods COVID-19 infection was confirmed at enrollment with a positive antigen or PCR test. Baseline demographics and medical histories were collected from participants at enrollment and daily self-reported symptom questionnaires were obtained to assess symptom severity and duration. Risk factors associated with symptom severity and duration were determined by multivariate logistic regression and Cox proportional hazards model. Results Two hundred and forty one participants meeting the eligibility criteria were enrolled, including 174 confirmed COVID-19 cases (9% Delta and 90% Omicron), 33 ILI cases, and 34 healthy contacts. COVID-19 participants had a shorter median symptom duration of 9.0 (95% CI, 8.0–11.0) days than ILI participants. Infection with the Delta variant resulted in a longer symptom alleviation period compared to infection with the Omicron variant. The most commonly reported symptoms among COVID-19 participants were reported in the nasal and chest/respiratory domains of the FLU-PRO Plus. Participants infected with the Delta variant reported more symptoms overall, with significantly more symptoms affecting eyes and senses reported. 55% of SARS-CoV-2-positive participants reached a negative N1 Ct value by the day 14 study time point. No risk factors for moderate to severe symptoms were identified in this outpatient cohort. Male sex was associated with a shorter symptom duration. Conclusion Symptom manifestation varied among Delta and Omicron variants. Few risk factors were identified for increased symptom severity or duration.